Description of three new species of Grandilithus Liu & Li, 2022 (Araneae: Phrurolithidae) from China - Shi, Songtao; Mu, Yannan; Zhang, Feng (Zootaxa, 2025)
Three new species of Grandilithus Liu & Li, 2022 (Araneae: Phrurolithidae) are described from China on the basis of both sexes: G. globosus sp. nov. from Anhui Province, G. nigromaculatus sp. nov. from Guangdong Province, and G. tongren sp. nov. from Guizhou Province. Detailed descriptions, photographs, and a distribution map for these species are provided. In addition, Grandilithus is divided into three species-groups based on the genitalic characters.